Valuasi Ekonomi Ekosistem Mangrove dan Kontribusi Mangrove Terhadap Pendapatan Rumah Tangga - Mega Lugina; Indartik Indartik; Mirna Aulia Pribadi (Jurnal Penelitian Sosial dan Ekonomi Kehutanan, 2019)
Mangrove forests have social, economic, and ecological functions to surrounding communities. Government policies in managing mangroves will affect its sustainability. Often, mangrove ecosystems become the main target to  be  converted  for  “non-forestry”  development  because  they  are  mistakenly  considered  to  have  little  or  no benefits. Therefore, it is necessary to calculate and to inform total economic value of mangrove ecosystems, so that if the function is disrupted due to conversion, the amount of loss that will be known. This paper aims to calculate the total economic value of mangroves and its contribution to household income using economic valuation. Results showed that the benefits of mangrove ecosystems in Kutawaru, Pemogan, and Tuban villages consisting of direct benefits (fish, crabs, shrimps, and tourism), indirect benefits (wave breakers), and option use (biodiversity value). Potential total economic value of mangroves in Kutawaru, Pemogan, and Tuban villages are Rp54.1 millions/ ha/year, Rp17.4/millions/ha/year, and Rp26.6 millions/ha/year respectively. In all three sites, indirect use value contributes the highest to the total economic value, often this value is not taken into account when considering ecosystem benefits. The highest contribution of mangrove ecosystems to the total household income is in Kutawaru village  with  amount  of  Rp1.4  millions/month/household.  In  addition  to  the  total  economic  value,  community dependence on mangroves must be considered by the government in managing mangrove ecosystems.